Personal branding strategy for non-incumbent candidates: A case study of Lita Machfud Arifin in the 2024 East Java electoral district 1 election contest: Strategi personal branding kandidat non-petahana: Studi kasus Lita Machfud Arifin dalam kontestasi elektoral Dapil Jawa Timur 1 tahun 2024 - Felisa Dwita Rahmawati; Kacung Marijan (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2026)
This study analyzes personal branding strategies in electoral competition through the success of Lita Machfud Arifin (LMA) as a non-incumbent candidate from the NasDem Party in the 2024 Indonesian House of Representatives election in the highly competitive East Java 1 electoral district. The research employs a qualitative approach using a case study method and the framework of The Eight Laws of Personal Branding by Peter Montoya. Data were collected through in-depth interviews, observation, and digital documentation. The findings indicate that LMA’s personal branding success was determined not only by political communication strategies but also by social capital and financial capital. LMA’s background as the wife of the former East Java Police Chief strengthened her existing social networks, while financial resources enabled a more independent and optimized campaign execution. The application of The Eight Laws of Personal Branding serves as a catalyst in enhancing visibility, differentiation, and emotional connection with voters. The synergy between personal branding and capital strength is reflected in the 68,456 votes that secured LMA the first DPR RI seat for the NasDem Party in the East Java 1 electoral district. This study concludes that personal branding is most effective when supported by strong social and financial capital.